Income redistribution in Latin America: A microsimulation approach - Cristina Arancibia Romero; Mariana Dondo; H. Xavier Jara; David Macas Romero; Nicolás Oliva; Rebeca Riella; David Rodriguez; Joana Urraburu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
We analyse the effect of taxes and benefits on income distribution of six Latin American countries: Argentina, Bolivia, Colombia, Ecuador, Uruguay, and Venezuela. Our analysis makes use of tax-benefit microsimulation models based on harmonized household representative survey data and developed within the structure of EUROMOD. The analysis focuses on the relative importance of tax-benefit instruments across countries and on the effect of taxes and benefits on poverty and inequality. The selected countries represent a wide range of cases in terms of the redistributive role of the tax-benefit system with Uruguay providing a large degree of redistribution, whereas the Bolivian system has a very modest role. We further exploit the advantages of our models and perform a simulation exercise whereby the most progressive income tax system of our set of countries is applied to the rest and assess its effect on inequality and revenue. Our paper represents the first study making use of microsimulation techniques to assess the redistributive role of tax-benefit systems in the region in a comparable manner, and highlights the advantages offered by microsimulation models to evaluate the effect of policy reforms aiming to improve social protection in the region.
Keywords: I32; I38; H24; D13; 330; taxes; benefits; microsimulation; Latin America